MET-Pyk2 Axis Mediates Acquired Resistance to FGFR Inhibition in Cancer Cells - Kitowska, Kamila; Gorska-Arcisz, Monika; Antoun, Dima; Zarczynska, Izabela; Czaplinska, Dominika; Szczepaniak, Adrian; Skladanowski, Andrzej C.; Wieczorek, Maciej; Stanczak, Aleksandra; Skupinska, Monika; Sadej, Rafal (Frontiers in Oncology, 2021)
Deregulation of fibroblast growth factor receptors (FGFRs) signalling, as a result of FGFR amplification, chromosomal translocation or mutations, is involved in both initiation and progression of a wide range of human cancers. Clinical data demonstrating the dependence of cancer cells on FGFRs signalling clearly indicate these receptors as the molecular targets of anti-cancer therapies. Despite the increasing number of tyrosine kinase inhibitors (TKIs) being investigated in clinical trials, acquired resistance to these drugs poses a serious therapeutic problem. In this study, we focused on a novel pan-FGFR inhibitor - CPL304110, currently being investigated in phase I clinical trials in adults with advanced solid malignancies. We analysed the sensitivity of 17 cell lines derived from cancers with aberrant FGFR signalling, i.e. non-small cell lung cancer, gastric and bladder cancer to CPL304110. In order to explore the mechanism of acquired resistance to this FGFR inhibitor, we developed from sensitive cell lines their variants resistant to CPL304110. Herein, for the first time we revealed that the process of acquired resistance to the novel FGFR inhibitor was associated with increased expression of MET in lung, gastric and bladder cancer cells. Overexpression of MET in NCI-H1703, SNU-16, RT-112 cells as well as treatment with HGF resulted in the impaired response to inhibition of FGFR activity. Moreover, we demonstrated that cells with acquired resistance to FGFR inhibitor as well as cells overexpressing MET displayed enhanced migratory abilities what was accompanied with increased levels of Pyk2 expression. Importantly, inhibition of both MET and Pyk2 activity restored sensitivity to FGFR inhibition in these cells. Our results demonstrate that the HGF/MET-Pyk2 signalling axis confers resistance to the novel FGFR inhibitor, and this mechanism is common for lung, gastric and bladder cancer cells. Our study suggests that targeting of MET/Pyk2 could be an approach to overcome resistance to FGFR inhibition.